COMPLEX OF PATHOGENES ON VEGETABLE CROPS IN CONDITION OF CENTRAL REGION OF RUSSIA - L. T. Timina; I. A. Engalicheva (Овощи России)
As a result of monitoring of causative agents of diseases of vegetable crops and studying of its species specification, the genus and species of fungi and bacteria, were found. Previously unknown in the Central region of Russia pathogens of carrot were identified: Sclerotinia nevales, Gleocladium roseum, Verticillium spp, Trichotecium roseum, Streptomyces scabies, F. nivale, F. chlamidosporum, F. equiseti, F. proliferatum, Chaetomium spp., Erysiphe umbelliferum, Erwinia carotovora. Main causative agents of diseases  of carrot during storage were also described: Alternaria infectoria, A. alternatа, A. arborescens, A. radicina, A. cheiranthi, A. corotiincultae, A. cinerariae, Embellisia spp., Nimbia spp., Cladosporium spp. It was found new pathogen for onion (Aspergillus niger), garlic (Fusarium semitectum, F. subglutinans, F. proliferatum, F.avenacium), red beet (Typhula ishikariensis), and radish (Drechslera Bondartseva).